Explaining Happy Victimizing in adulthood: A cognitive and economic approach - Minnameier, Gerhard (Frontline Learning Research, 2020)
While acknowledging the phenomenon of “happy victimizing” (HV), the classical explanation is questioned and challenged. HV is typically explained by a lack of moral motivation (MM) that is thought to develop in late childhood and adolescence. Apart from empirical evidence for widespread HV in adulthood, there are also strong theoretical arguments against the classical explanation. Firstly, there are arguments against the coherence of the very concept of MM. Secondly, while the classical explanation focuses on internal drivers (in the sense of MM), the one proposed in the present paper focuses on the patterns of interaction. Accordingly, HV may depend less on internalised values and individual motivation (whether in terms of moral internalism or moral externalism), and more on the “rules of the game” that are established in social interaction (or not). On this account, HV appears where higher order moral rules are not established and cannot be established, either due the circumstances or due to the unwillingness (or incapability) to play by the rules of these higher order games (where “games” are to be understood in the game-theoretic sense). The ordinary one-shot prisoners’ dilemma is a case in point. It precludes promise-giving as well as other higher order moral regimes, but instead forces the agents into a conflict of interest, where everyone has to mind their own business. Moreover, claiming that all players have to pursue their own self-interest, can be understood as moral rule of its own.